EFFECTIVENESS OF DIGITAL BASED ON ENTREPRENEURSHIP, MANAGEMENT – STARTUPS (CASE STUDY IN PONDOK PESANTREN SUNAN DRAJAT) - Surono, Surono; Rustono, Rustono; Soegito, A. T.; Rahardjo, Tri Joko; Faizin, M. Noor; Samsudin, Achmad (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effectiveness of digital marketing management through a startup based model. This research is a case study to determine the effectiveness of digital marketing through startups. This research is qualitative research with an ethnomethodology approach. The study was conducted by direct observation and in-depth interviews at the boarding school in Sunan Drajat Lamongan, East Java, which became a vendor and producer of goods in e-commerce start-up. Observations were made at the time of the transaction use of the start-up application which then conducted open interviews to obtain data on the effectiveness of digital marketing management. The results of observations and in-depth interviews in this study indicate that the effective management of digital marketing at start-up does indeed increase income from entrepreneurship at the Sunan Drajat boarding school. Sunan Drajat’s entrepreneurship feels an increase in income with startup based marketing management.